Determinants and Consequences of Financial Constraints: A Review of the Empirical Literature - Habib A; Costa M; Jia J (The Hong Kong Polytechnic University, 2021)
We synthesise the empirical literature on the determinants and consequences of financial constraints in the disciplines of accounting and finance, critique the findings, and offer suggestions for future research. A prolonged run of financial constraints can eventually lead to corporate failure, because a company’s financial performance depends on its ease of access to external financing. Determinants of financial constraints encompass firm-level fundamental, macro-economic, and corporate governance variables, with an overwhelming majority of papers using the investment-cash flow sensitivity model for measuring financial constraints. We also review the empirical literature on the consequences of financial constraints. Financial constraints lead to higher cash holdings, less asymmetric cost behaviour, and fewer innovations. Constrained firms also use income-increasing accruals more aggressively than unconstrained firms do. Finally, financially constrained firms avoid taxes in order to produce temporary cash tax savings.
Keywords: Financial Constraints; Investment-Cash Flow Sensitivity; Corporate Governance; Financial Reporting; Cash Holdings